ĐẶC ĐIỂM HÌNH THÁI VÀ THÀNH PHẦN HÓA HỌC CỦA ZIRCON TRONG GRANITOID KHỐI NÂNG PHAN SI PAN: Ý NGHĨA CỦA CHÚNG TRONG VIỆC XÁC ĐỊNH NGUỒN GỐC ĐÁ VÀ LỰA CHỌN CHO PHÂN TÍCH ĐỒNG VỊ - Dung, Phạm Thị; Hòa, Trần Trọng; Anh, Trần Tuấn; Phượng, Ngô Thị; Ý, Nguyễn Viết; Hằng, Hoàng Thị Việt; Thương, Vũ Thị; Ly, Vũ Hoàng (Vietnam Journal of Earth Sciences, 2011)
Morphology and chemistry of zircon from Phanerozoic granitoids in Fansipan uplift: their significance in determination of rock type and select for isotopic analysis Based on morphological characteristics and chemical composition of zircon in the Phanerozoic granitoids in Fansipan uplift, identificable signatures of primary zircon inigneous rocks are initially established. On morphological characteristics: zircon crystals intact crystal shape with two pointed edges (tetragonal prism or pyramid crystals), is quite clear, usually colorless, yellow-brown, brown-pink color,.. Chemical characteristics of zircon: HfO2 <2%, the Zr/Hf ratio in zircon from 17 to 380, these values prove the magmatic origin and correlate with the high total alkaline rocks: syenite, nepheline syenite, granosyenite,.. These characteristics have to be noted in the selection process for zircon isotopic analysis. Based on geochemical characteristics, zircon of two rock types are initially distinguished: 1/ Zircon in I-type granite (consist of granosyenite, alkaline granosyenite, quartz syenitodiorite, syenite,....), characterized by: HfO2 content < 2 wt.%, the Zr/Hf ratio is high (>100), the Hf/(Hf + Zr) ratio <0.025; and 2/ Zircon in A-type granite (afvedsonite bearing granite), characterized by: HfO2 content > 2.5 wt.%, low Zr/Hf ratio (<20), Hf/(Hf + Zr) ratio >0.025, and ThO2 and UO2 content tends to be higher than the first type.